Hugh Fearnley-Whittingstall: The River Cottage Cookbook - Davidson, Alan E (Petits Propos Culinaires, 2024)
Hugh Fearnley-Whittingstall: The River Cottage Cookbook: HarperCollins, 2001: ISBN 0-00-220204-2:448 pp., photographs by Simon Wheeler, h/b, £19.99.